Yona of the dawn. 45 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2025)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! Yona and Hak return to Kyuto in pursuit of Yellow Dragon Zeno, hoping to stop him from succeeding at his plan to end his life. As they make their way through the ravaged capital, the two head toward Hiryuu Palace, the place where Zeno's immortality originated..."--